The Maine, the Romney and the Threads of Conspiracy in Cuba. (1st December 2015) - Paul Ryer
Abstract : What constitutes a conspiracy, and what are the stakes of popular theories of conspiracy? This article addresses these questions through an ethno-historical examination of narratives about conspiracies endured and posited by Cuban people. Long before the Revolution in 1959, continuing through the Fair Play for Cuba Committee, numerous assassination attempts against Fidel Castro, and onward to recent claims of biological warfare orchestrated by the government of the US, conspiracy theories have circulated widely in Cuba and its diasporic enclaves. Drawing on ethnographic and historical data, the article embeds present-day narratives of conspiracy in the longer-run history of Cuban conspiracy theories such as those initially presented in the case of the USS Maine and its nineteenth-century precursors, notably including the stationing of the HMS Romney in Havana harbour, and the so-called conspiracy of La Escalera in 1844. It argues, ultimately, that these tales are always morality tales, counterposing nefarious agents of an illegitimate external power to the imagined community of those (including the narrator's self and audience) thus disenfranchised. In that sense, then, the truth value of any particular account of conspiracy is irrelevant to the larger truth of Empire.